ACCOUNTING INFORMATION SYSTEM QUALITY AND MANAGEMENT INFORMATION SYSTEMS INTEGRATION: A PATHWAY TO ENHANCED FINANCIAL RISK MANAGEMENT - Md Zillul Karim (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the integration of Accounting Information Systems (AIS), Management Information Systems (MIS), and Financial Risk Management (FRM) into a unified dashboard to enhance financial reporting accuracy, operational efficiency, and strategic decision-making in complex organizational environments. Method: The study adopts a conceptual and analytical review approach by synthesizing relevant literature on information systems integration, financial risk management frameworks, enterprise architectures, and emerging digital technologies. Key themes related to system interoperability, real-time reporting, predictive analytics, and governance mechanisms are systematically analyzed to develop an integrated conceptual framework. Results: The findings indicate that AIS–MIS–FRM integration enables consistent data flow, real-time financial insights, and early warning mechanisms for liquidity and market risks, thereby supporting proactive monitoring and regulatory compliance. The use of integration architectures such as Service-Oriented Architecture (SOA) and Enterprise Service Bus (ESB), along with artificial intelligence (AI), machine learning (ML), and Risk Management Information Systems (RMIS), significantly enhances risk prediction and decision quality. System quality, information reliability, and professional expertise of accountants emerge as critical success factors. Novelty: This study contributes by presenting a holistic dashboard-based integration model that aligns technology, governance, and data intelligence to transform traditional financial management into a proactive, data-driven, and strategically adaptive system.